Analysis of Information Sharing and Trust on Supply Chain Performance at PT. Lamong Energi Indonesia - M.Hasby Assiddieqy; Maya Syaula; Siswa Pratama (Universitas Dehasen Bengkulu, 2026)
The study aims to determine whether Information Sharing and Trust partially and simultaneously have a positive and significant impact on Supply Chain Performance at PT. Lamong Energi Indonesia. The sample is 40 respondents, The results of the study indicate that Information Sharing has a positive and significant impact on Supply Chain Performance at PT. Lamong Energi Indonesia. Tested and acceptable based on the t-value of the Information Sharing variable (X1) is 3.618 and the t-table value is 2.008, so t-count>t-table (3.618>2.008) and the Sig. value. <0.01 The magnitude of the impact of Information Sharing (X1) on Supply Chain Performance (Y) is 0.369, Trust has a positive and significant impact on Supply Chain Performance. Tested and acceptable based on the t-value of the trust variable (X2) is 3.251 and the t-table value is 1.997, so t-count>t-table (3.251>1.997) and the Sig. value. <0.02. The magnitude of the impact of Trust (X2) on Supply Chain Performance (Y) is 0.383, Trust has a positive and significant effect on Supply Chain Performance at PT. Lamong Energi Indonesia. Information Sharing and Trust simultaneously have a positive and significant impact on Supply Chain Performance. Tested and acceptable based on the F count value of 11.332 with a significance level of 0.000, greater than the F table value with a significance level of 95% (α = 0.05).